Antiviral Peptides Derived from Plants: Their Designs and Functions - Feyzyab, Haleh; Fathi, Nikoo; Bolhassani, Azam (Protein and Peptide Letters, 2023)
In recent years, plant-derived bioactive compounds have been developed as antiviral agents. Plants synthesize a variety of compounds, especially peptides, which possess antimicrobial activity. Current studies have shown that some antimicrobial peptides have antiviral activity against a wide range of human DNA and RNA viruses and play an effective role in the treatment of human viral diseases. These peptides act through different mechanisms. They can integrate into the envelope of the target virus or cell membrane of the host, resulting in an unstable membrane. For instance, some peptides prevent the attachment of viral spike proteins to host cells. On the other hand, some peptides may alter the cellular pathways, including DNA replication or protein synthesis, leading to the suppression of viral infection. However, the antiviral activity of peptides can be affected by their chemical and structural properties. In several studies, the properties of antimicrobial (antiviral) peptides were altered by minor modifications, but these changes require tools to predict. Recently, computational approaches have been introduced to analyze the effects of structural modifications on the physicochemical properties, mechanism of action, stability, and activity of peptides. In this mini-review, we will describe the design and function of antiviral peptides derived from plants.
Keywords: Antimicrobial peptides